2018
DOI: 10.3892/etm.2018.6621
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of hypoxia inducible factor‑1α promoted progression of diabetic nephropathy with hypertension

Abstract: The present study was designed to investigate the effect of hypoxia inducible factor-1α (HIF-1α) on diabetic nephropathy (DN) with hypertension. HIF-1α deficient mice (Mx/HIF-1α) were constructed and treated with streptozotocin (STZ) injection for hypertensive DN induction. Normal C57BL/6 mice received STZ or no treatment (normal) were considered as controls. Three days post STZ administration; body weight, fasting blood glucose (FBG), 24 h urinary albumin and systolic blood pressure (SBP) were measured weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
(35 reference statements)
2
14
1
Order By: Relevance
“…Furthermore, gut microbiota has been shown to play a role in the regulation blood pressure (Li et al, 2017;Marques et al, 2017;Ma and Li, 2018;Toral et al, 2019). Although Lassila et al did not observe differences in systolic blood pressure in the setting of diabetes as in the current study, this effect has been observed by others (Zhong et al, 2015;Jiao et al, 2018).…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, gut microbiota has been shown to play a role in the regulation blood pressure (Li et al, 2017;Marques et al, 2017;Ma and Li, 2018;Toral et al, 2019). Although Lassila et al did not observe differences in systolic blood pressure in the setting of diabetes as in the current study, this effect has been observed by others (Zhong et al, 2015;Jiao et al, 2018).…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, Epo and the activation of its receptor decrease albuminuria, mesangial expansion and renal fibrosis [ 55 , 56 , 57 ]. Other studies have shown that overexpression of HIF-1α in tubular epithelial cells contributes to the progression of renal fibrosis, and the inhibition of HIF-1α expression prevents the progression of renal fibrosis and attenuated DN progression [ 19 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been hypothesized that OS modulates hypoxic factors. Hypoxia inducible factor-1α (HIF-1α) is the main regulator of cellular response to hypoxia modulating multiple cellular processes in the kidney [ 15 , 19 ]. Under hypoxic conditions, HIF-1α modulates apoptosis, autophagy, inflammation, and cell cycle arrest, among other cellular mechanisms that are involved in renal protection [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, hypoxic tubular cells activate the adaptive process for the survival against tissue hypoxia. 15 Hypoxia-inducible factor−1alpha (HIF-1α) is a key protein that plays a major role in modulating the reaction of tissue to hypoxia, HIF-1 has a heterodimeric structure consists of oxygen-sensitive HIF-1alpha subunit bound to constitutively expressed Beta (β) subunit that subsequently activates the HIF-response element (HRE) pro-survival genes that enhance oxygen delivery in hypoxic organs such as brain, heart, liver and kidney, [15][16][17] but its function is depressed in diabetes. 18,19 Although studies have shown that overexpression of HIF-1α in tubular epithelial cells contributes to renal fibrosis, its inhibition prevented the progression of renal fibrosis and attenuated diabetic kidney disease.…”
Section: Introductionmentioning
confidence: 99%